Identiti masyarakat peribumi dalam seni tampak di Malaysia : satu kaedah memasyarakatkan seni? - Jonlain, Anak Liam. (Universiti Malaysia Sarawak (UNIMAS), 2006)
My artistic exploration deals with unpopular cultural objects of the minority ethnic community. The artist adopted a plaited object known as Samayor in his endeavour to transform cultural object into contemporary value.